STUDYING PHYSICAL AND MECHANICAL PROPERTIES WHEN PROCESSING BINARY POLYMERS (Web of Teachers: Inderscience Research, 2024)
Among man-made waste, polyvinyl chloride (PVC) accounts for 60% of the total amount of polymer waste. Recycling PVC waste is a bit complicated, so the products made from it have a complex chemical composition, that is, various additives will be added.